SISTEM CERDAS TES KEPRIBADIAN KRAEPELIN - Nurhasan, Usman; Suryani, Debhys; Amalia, Eka Larasati (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
Psychotest test becomes an important need in various human life space. Not only related to things that are clinical, psychotest test is also used in work space. Psychological test is implemented as an effort to know by recognizing ones personality further. One of method used psychologist is Kraepelin to get the types of personality. In practice, psychological tests in understanding an object that is human with all the attitudes and behavior is still using the old method. Psychological tests still use sheet or question series given to related objects and the calculation of the results or scoring still done manually. Error in scoring will affect the result so that will lead to the perception that is not appropriate.Assessment Kraepelin can be formed with an intelligent system with the approach method of Fuzzy Inference System, with the basis of experience in the field of psychology.Fuzzy Inference System will be the brain in analyzing the scoring which is a representation of the thinking of an expert, in this case the psychologist.Sistem is web-basedwhich provide personality test results and also provide information about the types of personality that exists.Keyword : expert system, kraepelin, fuzzy inference system